The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.sxmr.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Women with Colorectal/Anal Cancer

Abstract: Introduction: Treatments for colorectal and anal cancers can have a detrimental impact on sexual function. Type of treatment, which may include surgery, radiation and/or chemotherapy, varies by disease site and severity. Treatment and long-term side effects can impact sexual function and intimacy for patients and their partners. Aim: To review the literature regarding treatment for colorectal/anal cancer and its impact on female sexual function, and to provide an assessment of medical outcomes and patient-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…1st quartile: <=14.5 (least active), 2nd quartile: 14.5-26, 3rd quartile: >26-43.8, 4th quartile (most active): >43.8. 7 Comorbidity is classified according to a modified the Charlson Comorbidity Index (CCI), excluding cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1st quartile: <=14.5 (least active), 2nd quartile: 14.5-26, 3rd quartile: >26-43.8, 4th quartile (most active): >43.8. 7 Comorbidity is classified according to a modified the Charlson Comorbidity Index (CCI), excluding cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The physical late effects of CRC and its treatments are well known and include among other things gastrointestinal and urogenital problems [6], sexual dysfunction [7] and neuropathy [8,9]. This group of patients may also live with a colostomy as a result of the surgical intervention, giving rise to specific problems.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility and sexual health are also major concerns; however, 64% of survey participants indicated that a medical professional did not talk to them about fertility preservation during diagnosis or treatment [20]. Sexual dysfunction has been reported to be one of the most common longterm effects of CRC treatment [28] and may be of particular concern for young adult patients [29]. Based on these data, we identified psychosocial services, fertility, and sexual health as the key clinical programmatic elements.…”
Section: Developing a Young Onset Colorectal Programmentioning
confidence: 99%
“…Existing research has mainly focused on women who have breast or gynecological cancer (Chen et al, 2018;Ljungman et al, 2018;Condorelli et al, 2019) and men who have prostate cancer (Cakar et al, 2013;Fode et al, 2017;Clavell-Hernández et al, 2018) as well on mixed populations such as colon cancer patients (Canty et al, 2019;Stulz et al, 2020). Some cancer types, including gynecological or prostate cancer directly affect the sexual organs.…”
Section: Introductionmentioning
confidence: 99%